Increasing Interest to Pursue Tertiary Education among School Leavers in Indonesia: a Strategic Analysis - Izzah Illiyyina; Aulia Regita Dewi Fitriana; Nabila Septia Rosa; Ananda Helena Nurul Izzah; Fadilah Puteh (JIE (Journal of Islamic Education), 2025)
This article aims to understand the challenges of the need for more interest in pursuing higher education among school leavers in Indonesia. The research method is qualitative with case study approach. The researcher uses document analysis to gather relevant data from primary and secondary sources like articles, news stories, and reports. Data analysis techniques using strategic management tools such as PEST, McKinsey 7S, SWOT, and TOWS. The analysis identifies key strengths, weaknesses, opportunities, and threats within the educational landscape. The findings highlight the Ministry's strengths in strategic planning, skill development initiatives, system implementation, leadership effectiveness, adherence to shared values, and a well-established workforce. However, challenges remain, particularly in adapting to political transitions, optimising curriculum design in rural areas, and managing budgetary constraints. The TOWS matrix analysis provides strategic recommendations to address the low tertiary education enrollment rate among school leavers. Proposed strategies include innovations in human resource development, prioritisation of 3T (frontier, outermost, and disadvantaged) regions, rural outreach programs, and salary structure evaluations focused on development. The successful implementation requires strategic planning, stakeholder engagement, pilot programs, robust monitoring and evaluation, adequate budget allocation, capacity building, continuous improvement mechanisms, and public awareness campaigns. These efforts aim to create a more inclusive education system that empowers individuals across diverse backgrounds and geographical locations, ultimately enhancing Indonesia's educational landscape.